Force-sensorless human joint impedance estimation utilizing impulsive force. (19th March 2021) - Yagi, K.; Mori, Y.; Mochiyama, H.
ABSTRACT: The paper is concerned with force-sensorless estimation of human joint impedance utilizing an impulsive force. We analyze the dynamic response of a human joint induced by the impulsive perturbation and derive the relationship between the amplitude of the perturbation force and the initial value of the induced angular velocity. This relationship means that the force amplitude required by the estimation algorithm can be replaced with a specific value of the velocity, which leads to eliminating the need for force-sensing. In order to verify the force-sensorless impedance estimation experimentally, a wearable-type snap-through buckling mechanism is employed as the impulsive force generator. The experiments are carried out with a benchmark setup and a healthy male participant. The impedance estimation has been achieved without using any force sensor and performs good consistency with the specific mechanical impedance of the setup and with the ankle impedance reported by related works respectively. The obtained results thus indicate the feasibility of the proposed force-sensorless scheme. GRAPHICAL ABSTRACT: